Is It Live or Is It Internet? Experimental Estimates of the Effects of Online Instruction on Student Learning - Figlio, David; Rush, Mark; Yin, Lu (Journal of Labor Economics, 2013)
This article presents the first experimental evidence on the effects of live versus Internet media of instruction. Students in a large introductory microeconomics course at a major research university were randomly assigned to live lectures versus watching these same lectures in an Internet setting where all other factors (e.g., instruction, supplemental materials) were the same. We find modest evidence that live-only instruction dominates Internet instruction. These results are particularly strong for Hispanic students, male students, and lower-achieving students. We also provide suggestions for future experimentation in other settings.